Reformasi Birokrasi Di Badan Pusat Statistik Kota Palembang - Wahyuli, Yofitri Heny; Sukhaidi, Sukhaidi; Sari, Dian Novita Fajar; Anggleni, Andela (JPAP: Jurnal Penelitian Administrasi Publik, 2022)
This research is a policy study that discusses the efforts of the Central Statistics Agency for the City of Palembang in implementing bureaucratic reform. Based on the results of this study, the results of research and discussion show that this study aims to analyze the implementation of Presidential Regulation Number 81 of 2010 concerning Bureaucratic Reform at the Palembang City BPS Office, and to gain an understanding of the meaning of Bureaucratic Reform for Palembang City BPS office employees. This research method is qualitative. Primary data were collected through observation and interviews, while secondary data were obtained from documentation and literature studies that were relevant to the research object. The parameters measured are based on the implementation model of bureaucratic reform from aspects that include aspects of the institution (organization), management and human resources of the apparatus. In its implementation, it still encounters various kinds of obstacles, the main obstacles are the coordination of the Palembang City BPS Technical Team is still not at the Palembang City BPS itself but is in other agencies. The process of bureaucratic reform is certainly still far from what is expected by the community. BPS Palembang City is expected to be able to solve the problems that have caused the creation of an effective and efficient government. In the end, this research shows that the implementation of bureaucratic reform at BPS Palembang City requires a more effective and efficient control and incentive system.